PSYCHOSOMATIC CHARACTERISTICS OF PATIENTS WITH RHEUMATOID ARTHRITIS AND GOUT - Khusainova Munira Alisherovna (Galaxy International Interdisciplinary Research Journal, 2022)
The results of a comparative analysis of the psychosomatic status of patients with rheumatoid arthritis and gout are presented. It is shown that in all patients with rheumatoid arthritis, the level of quality of life decreases regardless of the drug therapy. There were no signs of depression in patients with rheumatoid arthritis and gout. Patients with rheumatoid arthritis have an increased level of anxiety, most pronounced in the presence of a high degree of laboratory activity, III–IV radiological stages; restrictions of non-professional, professional activity and self–service (III-IV functional classes). Patients with gout positively assess the general state of health and physical functioning. The high level of joie de vivre, self-confidence, and positive self-esteem found in patients with gout indicate an inadequate assessment of the severity of the disease and, as a consequence, low adherence to treatment, which correlates with hyperuricemia.